Notulae ad floram Sloveniae - Dakskobler, Igor (Hladnikia (Ljubljana), 1997)
New localities in the Julian Alps
Keywords: fitogeografija; flora; florae; phytogeography; Slovenia; Slovenija; vegetacija; vegetation